An Analysis of Transboundary Water Resources: A Case Study of River Brahmaputra - Bhattarai, Debi Prasad (Journal of the Institute of Engineering, 2009)
The need for water management on hydrological boundaries is mainly triggered by the growing competition for water or by the need to cooperate in an upstream downstream relation. For an institution operating on political boundaries, not coinciding with the boundaries of the river basin, it is very difficult to allocate or prioritise water or carry out flood control measures. A system of water management on political boundaries will induce the respective authorities to either monopolise the water supply sources within its area and to transfer the problem of flooding to downstream. In this article it is attempted to explore the major transboundary issues that need to be addressed in the whole Brahmaputra River basin. Sharing of resources, sharing of basic data and information and protection and preservation of ecosystem are identified as three major issues. In this context, controversial legal issues between the riparian nations in the past were also analysed which has triggered the scope for integrated approach to manage the Brahmaputra River basin. In the later part of the article, a critical analysis was made to understand the principles, approaches and instruments to address the above problems. Finally, some legal materials are presented which could be used as a basis for solving the major river basin issues. Key words: water management; diversifying water supply sources; water management strategies; Nepal Journal of the Institute of Engineering, Vol. 7, No. 1, July 2009, pp. 135-141 doi: 10.3126/jie.v7i1.2072